Helipot Model 63PR5K Helitrim trimming potentiometer (1950)
Potentiometers regulate the flow of electricity, like the volume dial on a radio. In 1940, Arnold O. Beckman was unsatisfied with dials on the market, so he designed his own helical potentiometers, or helipots, for use in his popular pH meter. The precision of this dial caught the eye of the MIT Radiation Laboratory’s secret radar project during World War II. Beckman redesigned the helipot to meet the needs of the United States military and set up a separate company, also called Helipot, to keep up with the demand for these knobs. In the 1950s, Helipot was reincorporated into Beckman Instruments as the Helipot Division and continued to make potentiometers and other electrical components for decades, those tiny dials becoming staples of the electronics manufacturing industry.
Keywords: Potentiometer; Beckman Instruments, Inc.